1983
DOI: 10.1037/h0080742
|View full text |Cite
|
Sign up to set email alerts
|

Etude ontogénétique de la coordination visuo-manuelle.

Abstract: RESUME Le developpement de la coordination visuo-manuelle est considere, a travers le modele du pointage de cible, comme un aspect du comportement de prehension d'un objet reunissant les composantes de localisation, d'approche et d'ajustement. Les differents parametres de ce modele -temps de reaction, temps de mouvement, erreur spatiale terminale -sont etudiees en relation avec les operations qui y sont respectivement associees en priorite. De plus, sont relevees certaines etudes sur le comportement adulte con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0
1

Year Published

1984
1984
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 37 publications
3
7
0
1
Order By: Relevance
“…Results showed an age-related increase in learning speed as well as an improvement of both accuracy and stability of the perceptual-motor pattern. These results are widely shared by literature with previous evidence in drawing [17], pointing [18], reaching [19] or intercepting [20] showing that substantial changes in perceptual-motor development in complex skills occur mainly between 5 and 12 years old.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Results showed an age-related increase in learning speed as well as an improvement of both accuracy and stability of the perceptual-motor pattern. These results are widely shared by literature with previous evidence in drawing [17], pointing [18], reaching [19] or intercepting [20] showing that substantial changes in perceptual-motor development in complex skills occur mainly between 5 and 12 years old.…”
Section: Introductionsupporting
confidence: 83%
“…In a set of pointing tasks, a nearly total absence of visually-based regulation of movement was shown in children aged from 5 to 7 years old. Then, from 7 to 12 years old, visually-guided regulation of the movement progressively increases with age [19]. It was also shown that stability of motor performance significantly improves after the age of 7 [21][23] as does accuracy [18], [20], [23], [24].…”
Section: Introductionmentioning
confidence: 92%
“…Thus, early after movement initiation, movements performed along one's midline were initially less variable than other straight-ahead movements as well as movements originating from or directed along one's midline. Discussion As expected (Bard & Hay, 1983;Bard et al, 1985;Bédard & Proteau, 2001;Bock 1993;Lhuisset & Proteau, 2002;Pellizzer & Hauert, 1996;Proteau et al, 2000), straight-ahead movements performed along one's midline were directionally more accurate and less variable than movements initiated from the same starting base but aimed at targets located 20°and 40°to the right. Our first goal was to determine why.…”
Section: Coefficient Of Extent Variability At Key Kinematic Landmarksmentioning
confidence: 51%
“…Eccentric targets typically show both larger endpoint variability than 0° targets as well as bias to the left of targets located to the left of the participants' midline and to the right of targets located to their right (Pellizzer & Hauert, 1996; Proteau & Isabelle, 2002). This is the case for both adults (Bard, Hay, & Fleury, 1985; Bédard & Proteau, 2001; Bock 1993; Proteau, Boivin, Linossier, & Abahnini, 2000) and children (Bard & Hay, 1983; Pellizzer & Hauert, 1996), and for both manual aiming (Bard & Hay, 1983; Bard et al, 1985) and video-aiming (Bédard & Proteau, 2001; Proteau et al, 2000) movements for which one's hand is represented by a cursor illustrated on a computer screen. In these studies, the starting base from which all movements were initiated was located directly in line with the participant's midline (Bard & Hay; Bard et al; Bédard & Proteau; Proteau et al).…”
mentioning
confidence: 99%
“…Avant l’âge de 7 ans, les enfants utilisent très peu les informations proprioceptives pour contrôler et corriger le déroulement d’une action (Babinsky, Braddick & Atkinson, 2012; King, Oliveira, Contreras-Vidal & Clark, 2012) en raison de la faiblesse supposée de l’acuité proprioceptive chez les enfants d’âge préscolaire (Laszlo & Bairstow, 1980; Shumway-Cook & Woollacott, 1985; Sigmundsson, Whiting & Loftesnes, 2000; Von Hofsten & Rösblad, 1988). Malgré une forte amélioration de l’acuité proprioceptive entre 4 et 7 ans, les enfants de 7 ans régulent le déroulement de l’action réelle en privilégiant massivement les réafférences visuelles sans intégrer les informations proprioceptives issues du mouvement (Bard & Hay, 1983; Van Roon, Caeyenberghs, Swinnen & Smits-Engelsman, 2008). Enfin, ce n’est qu’aux alentours de 9 ans que les enfants deviennent en mesure d’intégrer les informations visuelles et les informations proprioceptives dans le contrôle du mouvement (Chicoine, Lassonde & Proteau, 1992; Contreras-Vidal, 2006; Ferrel-Chapus, Hay, Olivier, Bard & Fleury, 2002; Van Roon et al, 2008; Von Hofsten & Rösblad, 1988).…”
unclassified